2021
DOI: 10.1002/jor.25199
|View full text |Cite
|
Sign up to set email alerts
|

No effects of early functional mobilization on gait patterns after acute Achilles tendon rupture repair

Abstract: This study aimed to compare recovery of gait patterns in patients treated with early functional mobilization (EFM) or standard treatment (ST) after Achilles tendon rupture repair. Second, this study aimed to explore associations between gait patterns and tendon elongation and calf muscle atrophy, respectively. Forty-seven patients (12 females), mean age 38.7 (7.3) years, were included. Patients were postoperatively randomized to EFM (n = 29), including immediate weightbearing and ankle motion for 6 weeks, or S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For example, researchers have established a rat model of ATI to examine the mechanism of ectopic ossification; the endothelium–mesenchymal transition is central to the pathological process ( 28 ). In animal studies and basic medical research, the development of computer hardware has greatly contributed to the study of heel ATI, allowing for a more comprehensive assessment of Achilles tendon repair and function in terms of the gait analysis ( 29 ) and elastography. Shear wave elastography (SWE) is a powerful tool for estimating tissue stiffness and sensitive to the early detection or monitoring of the tendinopathy ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers have established a rat model of ATI to examine the mechanism of ectopic ossification; the endothelium–mesenchymal transition is central to the pathological process ( 28 ). In animal studies and basic medical research, the development of computer hardware has greatly contributed to the study of heel ATI, allowing for a more comprehensive assessment of Achilles tendon repair and function in terms of the gait analysis ( 29 ) and elastography. Shear wave elastography (SWE) is a powerful tool for estimating tissue stiffness and sensitive to the early detection or monitoring of the tendinopathy ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cohort, and the results of repeated gait analyses, has been described previously. 8 In total, 47 patients were included, 29 who were treated with a dynamic orthosis (EFM) and 18 with ST 8 (Figure 1). Patient demographics are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…40 However, early weightbearing has not been found to be superior to standard care in the recovery of gait patterns early after ATR surgery. 2,8 Nevertheless, Costa et al 15 reported that early weightbearing after operative repair of an ATR resulted in a faster return to normal walking and stair climbing compared with immobilization. Deficits in calf muscle function are common after an ATR.…”
mentioning
confidence: 99%
“…There has been a general trend toward more patients being treated nonoperatively over the past decade or so as the advent of functional rehabilitation has improved on traditional results with nonoperative treatment 15 . However, much of the recent data on this subject have been highly variable, with differences in follow‐up time, rehabilitation techniques, outcome measures, and cohort size 17–24 . Furthermore, additional studies have shown no significant difference in rerupture and complication rates between the treatments 25 …”
Section: Introductionmentioning
confidence: 99%
“…15 However, much of the recent data on this subject have been highly variable, with differences in follow-up time, rehabilitation techniques, outcome measures, and cohort size. [17][18][19][20][21][22][23][24] Furthermore, additional studies have shown no significant difference in rerupture and complication rates between the treatments. 25 This systematic review focused on ATR treatment outcomes, with a specific focus on rerupture and complication rates, most notably wound issues.…”
Section: Introductionmentioning
confidence: 99%